THE MADIUN CITY GOVERNMENT'S LAPTOP PROCUREMENT POLICY FOR IMPROVING STUDENT MOTIVATION AND LEARNING ACHIEVEMENT IN ISLAMIC RELIGIOUS EDUCATION AND CHARACTER EDUCATION SUBJECTS - Abdul Zulfikar Ely; Sudarmadi; Afiful Ikhwan (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
The focus of this research is to explore data on policy efforts and any constraints in procuring laptops for the Madiun City Government towards increasing student motivation and achievement in the subject of Islamic Religious Education and morals at SDN 01 Taman Kota Madiun. This type of research is qualitative research, data collection techniques using observation, interviews and documentation, while data validity checking techniques use triangulation techniques: transferability, dependability, and confirmability. The results of the research: (1) The policy efforts implemented are (a) have been running for three years starting from 2020 from the pandemic period to now 2023 with a total of 237 units that are allowed to be taken home to support independent learning at home which is also balanced with installation wi-fi; (b) a special technician is prepared to be responsible for minor damage; (c) training of teachers to increase student motivation in Islamic religious education (PAI) subjects and manners which have an impact on students' enthusiasm during the learning process, facilitate the work of students' assignments independently, be responsible for individual student laptop maintenance, and increase achievement students with benchmarks for success are students who are more active in attending, doing assignments both during Covid and post-Covid, motivated to study independently with laptop facilities. (2) Obstacles in implementing this policy, in Islamic religious education (PAI) and morals subjects, namely (a) unstable (slow) network, especially in rural areas, (b) limited technicians who do not understand the problems in the PAI subject for needs application-based learning (software), (c) limited knowledge of the majority of Elementary School (SD) students in operating laptops effectively, (d) teachers who are still found not to focus on live explanations or giving material (not in accordance with lesson plans) online. While the impact of this policy is that teachers and students are proficient (literate) in technology, happy (motivated), increasing student achievement in terms of digital literacy using laptops in Islamic insight and also their character becomes responsible, so that achievement in learning increases